Investigation of in vitro amoebicidal activities of Ornithogalum sigmoideum on Acanthamoeba castellanii cysts and trophozoites (Annals of Medical Research, 2021)
None
Keywords: Acanthamoeba castellanii; Amoebicidal effect; Ornithogalum Sigmoideum.